OP0128 PTPN22 is Associated with Susceptibility to Psoriatic Arthritis but not Psoriasis: Evidence for a Further PSA-Specific Risk Locus. (9th June 2015) - Budu-Aggrey, A.; Lohr, S.; Bowes, J.; Uebe, S.; Bruce, I.N.; Feletar, M.; Marzo-Ortega, H.; Helliwell, P.; Ryan, A.W.; Kane, D.; Korendowych, E.; Alenius, G.-M.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory arthritis associated with psoriasis with a genetic component estimated to be larger than psoriasis alone. Recent studies have identified PsA-specific loci that begin to explain this increased burden, for example, amino acids in HLA-B and our own Immunochip study reported evidence for PsA-specific risk at chromosome 5q31 and IL23R . Methods: A total of 14 single nucleotide polymorphisms (SNP) were selected from our recent Immunochip study ( P <1x10 -4 ) to validate in 3, 139 PsA cases and 11, 078 controls from the UK, Republic of Ireland, Germany, Australia, Sweden and Italy using the Life Technologies QuantStudio genotyping platform. Association testing was performed using PLINK. For loci not previously reported for psoriasis we compare effect sizes using multinomial logistic regression, performed in Stata, and directly compare PsA genotypes from Immunochip (n=1, 936) to the psoriasis WTCCC2 study (excluding known PsA, n=1, 784). To control for phenotype misclassification with rheumatoid arthritis (RA), we include a genetic risk sore comprised of the 41 RA susceptibility reported in the RA Immunochip study as a covariate and re-analysed the PsA Immunochip. Results: We find genome-wide significant association to rs2476601, mapping to the gene PTPN22 ( P =1.49x10 -9, OR =1.32). There was no evidence for association to rs2476601 in the psoriasis WTCCC2 cohort ( P =0.34) and the effect estimates were significantly different between PsA and psoriasis ( P =3.2x10 -4 ). Direct comparison of genotypes for PsA and psoriasis found significant association to an increased risk of PsA ( P =4.4x10 -4, OR=1.3). The association to PTPN22 in the PsA Immunochip data was not affected by the inclusion of the RA-GRS as a covariate. In addition, we find genome-wide significant association to the previously reported psoriasis risk loci; NOS2 (rs4795067, P =5.27x10 -9 ). No other SNPs reached genome-wide significance in the combined dataset. Conclusions: For the first time, we report genome-wide significant association of PTPN22 (rs2476601) to PsA susceptibility. The risk allele (A) and direction of effect are consistent with previous reports for RA and type I diabetes, but opposite of that reported for Crohn's disease. We provide evidence that this is a PsA-specific risk locus as no association to psoriasis was observed in the WTCCC2 cohort and the effect estimates are significantly different between PsA and psoriasis when compared in multinomial logistic regression. Disclosure of Interest: None declared